1997
DOI: 10.1136/gut.40.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic beverages produced by alcoholic fermentation but not by distillation are powerful stimulants of gastric acid secretion in humans.

Abstract: Background-The effect of commonly ingested alcoholic beverages on gastric acid output and release of gastrin in humans is unknown. Aim and Methods-In 16 healthy humans the effect of some commonly ingested alcoholic beverages produced by fermentation plus distillation (for example, whisky, cognac, calvados, armagnac, and rum) or by alcoholic fermentation (beer,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
13

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 14 publications
(1 reference statement)
4
32
0
13
Order By: Relevance
“…In addition, we found that the alcoholic beverage constituents that stimulate gastric acid output and release of gastrin are produced during the process of fermentation and removed during the following process of distillation (7).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, we found that the alcoholic beverage constituents that stimulate gastric acid output and release of gastrin are produced during the process of fermentation and removed during the following process of distillation (7).…”
Section: Introductionmentioning
confidence: 99%
“…Pure ethanol in low concentrations (≤4% vol/vol) is a mild stimulant of gastric acid output, whereas at higher concentrations, it has either no effect or a mildly inhibitory one (5). Alcoholic beverages with low ethanol content (beer and wine) are powerful stimulants of gastric acid output and gastrin release; the effect of beer is equal to the maximal acid output (5)(6)(7)(8). Beverages with a higher ethanol content (e.g., whisky, gin, cognac) do not stimulate gastric acid output or release of gastrin (5,7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…W przypadku napojów alkoholowych wpływ na sekrecję żołądkową mogą mieć także inne związki chemiczne niż etanol. Z dotychczas opublikowanych badań wynika, że zwiększenie wydzielania kwasu w żołądku, a także uwalniania gastryny obserwuje się po wypiciu napojów alkoholowych pochodzą-cych z fermentacji, a niepoddanych procesowi destylacji (piwo, wino, szampan), natomiast napoje wymagające destylacji (whisky, koniak, rum) nie mają takiego działa-nia [59]. Oczywistą implikacją tej obserwacji jest dąże-nie do zidentyfikowania w napojach alkoholowych związków chemicznych odpowiedzialnych za działanie stymulujące sekrecję w żołądku.…”
Section: Wpływ Napojów Alkoholowych Na żOłądekunclassified